Determinants of Chinese direct investments in the European Union - Christian Dreger; Yun Schüler-Zhou; Margot Schüller (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
This paper analyses the determinants of Chinese direct investment (DI) in the European Union (EU). Evidence is based on panel Poisson models drawing on two investment monitors for individual projects. We distinguish between the numbers of greenfield investments (GIs) and mergers and acquisitions (M&As). The findings indicate that market size and trade relationships with China are the primary factors driving Chinese DI in the EU. In contrast, more business-friendly institutions do not foster DI. Chinese enterprises might be risk averse, in other words prefer to choose their activities in regions with less competitive markets. The striking difference between GIs and M&As is related to unit labour costs. Higher costs make the host country less attractive for the establishment of new firms, but do not affect the involvement in existing firms. The sectoral dispersion of Chinese DI in the EU has not changed much since the global financial crisis of 2008. Most relevant shifts have occurred in research and development (R&D), where low-income EU countries have gained in attractiveness.
Keywords: F21; E22; C25; 330; China FDI; Greenfield investments; mergers and acquisitions